Exploring Interpersonal Metafunction in an Electioneering Campaign Speech from Measuring Time (Helon Habila) - KOUTCHADE, INNOCENT SOUROU; AKPACA, SERVAIS MARTIAL; Awoyodo, Dieudonné (My University, 2020)
This study builds on the interpersonal meaning strand of the Systemic Functional Linguistics to highlight the suasive power of human language. In itemizing Lamang‘s electioneering campaign speech via such toolkits as mood, modality and personal pronouns, this paper employs a qualitative technique. It finds that the avalanche of mood types used by Lamang is made up of declarative clauses, which are echoed to convey information and convince the audience with positive facts. As to modal verbal operators, they are used to evince the speaker‘s adamant determination, and his unflinching commitment to move the whole country forward out of the dark ages and also build up his authority and selfishness. The prominent application of personal pronouns namely: ―we‖ and ―you‖ – ―we‖ patterns, is meant to create an intimate dialogic style which can shorten the distance between the speaker and the audience, weaken the power and maintain a reliant and equal relationship between them. This greatly helps to persuade the addressees. Overall, this paper attempts to set into the fore the orator‘s communicative alertness as he to shifts from braggardism or boastfulness to opportunistic humility depending on the context.
Keywords: Speech; Interpersonal metafunction; mood; modality; personal pronoun.